Analysis of Geprek Chicken Business Income (Case Study of Geprek Bossku restaurant in Poasia District, Kendari City) (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
This study aims to analyze the income, and business of Geprek Bossku restaurant. The research variables are (a) the characteristics of the respondents; (b) business profile; (c) investment costs; (d) production costs; and (e) acceptance. The research data were analyzed using income analysis, revenue, cost acceptance analysis (R/C Ratio), cost-benefit analysis (B/C Ratio), and depreciation expense. The results showed that the income earned at the Ayam Geprek Bossku restaurant business in Poasia District, Kendari City was Rp. 131.058.333/month.